2023
DOI: 10.1002/jobm.202300138
|View full text |Cite
|
Sign up to set email alerts
|

Histone deacetylase MrHos3 negatively regulates the production of citrinin and pigments in Monascus ruber

Abstract: Monascus spp. can produce a variety of beneficial metabolites widely used in food and pharmaceutical industries. However, some Monascus species contain the complete gene cluster responsible for citrinin biosynthesis, which raises our concerns about the safety of their fermented products. In this study, the gene Mrhos3, encoding histone deacetylase (HDAC), was deleted to evaluate its effects on the production of mycotoxin (citrinin) and the edible pigments as well as the developmental process of Monascus ruber … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…HOS3 in yeast has the specificity to H2AK7, H2BK11, H3K14, H3K23, H4K5 and H4K8 in vitro (Carmen et al., 1999 ; Gunderson et al., 2011 ; Trojer et al., 2003 ). By contrast, MrHOS3 has an obvious specificity to H3K9 and H3K18 in M. ruber (Liu, Zheng, et al., 2023 ). Detection of site‐specific acetylation reveals that UvHOS3 affects the acetylation levels of H3K9, H3K18, H3K27 and H4K8 in U. virens (Figure 5 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HOS3 in yeast has the specificity to H2AK7, H2BK11, H3K14, H3K23, H4K5 and H4K8 in vitro (Carmen et al., 1999 ; Gunderson et al., 2011 ; Trojer et al., 2003 ). By contrast, MrHOS3 has an obvious specificity to H3K9 and H3K18 in M. ruber (Liu, Zheng, et al., 2023 ). Detection of site‐specific acetylation reveals that UvHOS3 affects the acetylation levels of H3K9, H3K18, H3K27 and H4K8 in U. virens (Figure 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…In Monascus ruber , the deletion of Mrhos3 significantly elevates the acetylation levels of H3K9, H3K18 and H4K12. MrHOS3 negatively regulates the production of the mycotoxin citrinin and pigments (Liu, Zheng, et al., 2023 ). However, few studies have been reported on the roles of HOS3 in phytopathogenic fungi so far.…”
Section: Introductionmentioning
confidence: 99%